Redescription of the enigmatic Pronyssa hennigi (W. Horn), comb. nov. (Coleoptera: Cicindelidae) - Görn, Sebastian (Zootaxa, 2019)
When Walther Horn described Heptodonta hennigi from Assam in 1898, on the basis of a single female, he was completely uncertain about which genus he should classify this species in. He wrote that he could not identify the genus, but that the closest looking species he knew were Heptodonta tricondyloides Gestro, which is now placed in the genus Dilatotarsa Dokhtouroff, and Euryoda (= Prothyma Hope) lucidicollis Chaudoir. He was especially confused by the shape of the pronotum, but also by the lack of pubescens on the lateral margin of the metacoxae, which is a typical character for the genus Heptodonta Hope (see also Fowler 1912). Hence, twelve years later, Horn (1910) transferred hennigi to the Madagascan genus Physodeutera Lacordaire, which he regarded as a “group” of the genus Prothyma Hope. After more than eighty years, Wiesner (1992) placed the species in the Philippine Prothyma subgenus Symplecthyma Rivalier, but also indicated his classification as doubtful with a question mark. Cassola (2002) suggested for the first time a possible affiliation to the genus Pronyssa Bates. Just one year later, Karl Werner visited the collection Senckenberg Deutsches Entomologisches Institut in Müncheberg, Germany, and labelled the still only known specimen with the handwritten note: “Genus / Pronyssa! / Werner det’.03”.